Structural and electronic properties of GaN x As 1-x alloys - Baaziz, H.; Charifi, Z.; Ali Hussain, Reshak, Prof. Dr.; Hamad, Bothina A.; Yarub, Al-Douri (Springer-Verlag., 2013)
Link to publisher's homepage at http://www.springer.com/